Bell’s palsy and preeclampsia: case report - Cabrera, Santiago (2014)
Bell's palsy is a common neurological disorder whose frequency is increased three times in pregnant women. Its presence is associated with preeclampsia and hypertension. Diagnosis is eminently clinical and most appropriate treatment is prednisolone. We report a case of Bell's palsy in a 36-week pregnant woman with severe preeclampsia and gestational diabetes.